THE IMPACT OF CONSUMER ATTITUDE AND BRAND EQUITY TOWARD GREEN PURCHASE INTENTION FOR THE GREEN PRODUCT COSMETIC ON SARI AYU MARTHA TILAAR - Maradesa, Sysilia (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Â  Organic or green products such as food products, fashion products, personal care products, health products, etc, become focal attention of public in recent year. Purpose of this study are to determine the influence of consumer attitude and brand equity to green purchase intention for the green product cosmetic on Sari Ayu Martha Tilaar, also to determine the influence of consumer attitude and brand equity to green purchase intention for the green product cosmetic on Sari Ayu Martha Tilaar. This study is conducted in the people of Manado. This research will be held at June 2015. Recomendation is Sariayu Martha Tilaar in order to improve the intention to buy green products the company should focus first of all on the brand equity that the company should be able to make consumers can associate with the company's brand of green products that are environmentally friendly, organic, healthy, and sustainable. Â  Keywords: consumer attitude, brand equity, green purchase intention